Strategi Pemasaran Digital Pada Wisata Halal Di Cheria Halal Holiday Bandung - yassin, Yassin; Supriyadi (Jurnal Ekonomi Bisnis Manajemen Prima, 2025)
This study explores the implementation of digital marketing strategies at Cheria Halal Holiday Bandung, focusing on the rapidly growing halal tourism industry. The research examines how digital marketing strategies are used to enhance customer engagement, expand brand visibility, and support company growth in the halal tourism sector. A qualitative methodology was employed, including interviews, observations, and a literature review. The findings reveal that social media, search engine optimization (SEO), and blogger partnerships play a crucial role in raising brand awareness and attracting potential customers. While digital campaigns have effectively broadened market reach, challenges such as improved market segmentation and adapting to fast-changing digital trends remain. Based on these findings, it is recommended that Cheria Halal Holiday continue to strengthen its digital presence and adjust its marketing strategies to align with future trends in the industry